Global, regional, and national burden of low back pain in postmenopausal women from 1990 to 2021: a comprehensive analysis using data from the Global Burden of Disease Study 2021 - Xu, Jiaxian; Lei, Mingming; Xu, Dandan (Frontiers in Endocrinology, 2025)
BackgroundLow back pain (LBP) is a leading cause of disability worldwide, with its burden increasing due to population growth and ageing. Postmenopausal women are disproportionately affected, largely owing to estrogen decline, which accelerates osteoporosis and intervertebral disc degeneration. This study aimed to quantify the global, regional, and national burden of LBP among postmenopausal women from 1990 to 2021, using data from the Global Burden of Disease (GBD) Study 2021.MethodsWe analyzed prevalence, incidence, and disability-adjusted life years (DALYs) of LBP in women aged 55 years and older across 204 countries and territories from 1990 to 2021. Temporal trends were assessed using age-standardized rates (ASRs) and estimated annual percentage changes (EAPCs). Contributions of three modifiable risk factors—high body-mass index (BMI), smoking, and occupational or environmental exposures—were examined by Socio-demographic Index (SDI) quintiles.FindingsBetween 1990 and 2021, incident cases nearly doubled (from 35.2 million to 70.3 million), prevalent cases rose from 89.9 million to 176.8 million, and DALYs increased from 9.8 million to 19.1 million. Despite these increases, age-standardized incidence, prevalence, and DALY rates declined modestly. In 2021, the burden in postmenopausal women was 1.78 times higher for incidence, 1.86 times higher for prevalence, and 1.84 times higher for DALYs than in age-matched men. High BMI was the leading modifiable risk factor globally, contributing to 14.2% of DALYs, followed by occupational or environmental risks (12.6%) and smoking (7.3%). Regional variation was marked: high and high-middle SDI regions showed declining ASRs, whereas middle and low-middle SDI regions experienced increases.InterpretationThe global burden of LBP among postmenopausal women has risen substantially, despite declines in age-standardized rates. High BMI, occupational exposures, and smoking are key modifiable drivers, with varying impacts by development level. Public health strategies should prioritize weight management, workplace interventions, and smoking cessation, with particular focus on high-risk age groups and low-resource regions.